Teaching adventure education theory : best practices - Stremba, Bob, 1947-; Bisson, Christian A., 1964- (Champaign, Ill. : Human Kinetics, 2009)
Written for instructors who want their classroom experience to be as involving as the field, Teaching Adventure Education Theory offers activities instructors can use to help students make the connections between theory and practice. Top educators provide lesson plans that cover adventure theory, philosophy, history, and conceptual models. Teaching Adventure Education Theory: Best Practices offers stimulating, fun, and engaging activities instructors can use to assist future adventure educators, outdoor leaders, and group facilitators in making the connections between adventure theory and practice. Written for students and instructors who want their classroom experience to be as involving as the field environment, this professional reference features ready-to-use lesson plans that employ experiential education strategies for presenting the theory underlying the technical and facilitation skills required in leading adventure experiences. Editors Stremba and Bisson and leading adventure educators from the United States, Canada, Australia, and Japan provide an extensive perspective on teaching adventure theory, philosophy, history, and conceptual models through the use of activity-based learning. They offer a collection of 34 lesson plans that can be easily modified to fit individual teaching styles or student needs. Each lesson plan provides detailed activity instructions, teaching suggestions, and an overview of the theory taught in the lesson to provide the instructor with background conceptual material. An instructor CD-ROM, included with the text, contains student handouts, worksheets, and PowerPoint presentations to facilitate lesson implementation and assessment.
Teaching Adventure Education Theory presents experiential lesson plans covering such topics as these: •Instructional theory and curriculum design processes •History of adventure education •Educational and philosophical foundations of adventure education, including lessons on John Dewey's contributions •Central theories supporting common field practices, including optimal arousal theory, self-efficacy theory, attribution theory, and the flow theory •Leadership models and theories •Ethical and social justice issues •Group development and social psychology •Processing and facilitation models •The human-to-nature connection The book introduces core curriculum theories and models of adventure education, including a rationale on why students should know theory and how broader competencies within adventure education often align with colleges' liberal arts outcomes. It also explores the common pedagogical threads present in effective adventure education teaching processes and discusses the challenges and rewards of teaching adventure education. The book also provides a framework for implementing the lesson plans. Teaching Adventure Education Theory: Best Practices assists instructors in bringing to the classroom the experiential learning, critical reflection, and interdependent community that a challenging outdoor environment facilitates, helping students broaden their view of adventure education to encompass its theoretical dimensions.
Includes bibliographical references.
Keywords: Adventure education -- Study and teaching; Buitenactiviteiten; Ervaringsleren